Preparation method and application of transparent nanocellulose with high carboxyl content
Through the combination of sodium hydroxide pretreatment and multiple oxidants (Fenton reagent, TEMPO-NaBr-NaClO system and NaClO2), combined with high-pressure homogenization treatment, the limited carboxyl content in the preparation of nanocellulose in the prior art has been solved. Problem, the preparation of high-efficiency and safe high carboxyl content transparent nanocellulose is achieved.
Patent Information
- Application Number
- CN202411492489.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-09-27
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-11
AI Technical Summary
In the prior art, when preparing nanocellulose with high carboxyl content, the carboxyl content is limited, and re-oxidation or subsequent treatment is required, and no methods are used to use sodium hydroxide pretreatment and Fenton reagents.
The cellulose raw material was pretreated with sodium hydroxide, followed by Fenton reagent for the first step of oxidation, followed by TEMPO-NaBr-NaClO system and NaClO2 for the second and third steps of oxidation, and finally obtained high carboxylic groups by high pressure homogenization treatment. Content of transparent nanocellulose.
It significantly improves the oxidation degree and carboxyl content of cellulose, enhances the transparency of the product, expands its application range, and is simple to operate and safe, with a high product yield.
Smart Images

Figure CN119409842A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cellulose, and in particular relates to a method for preparing transparent nanocellulose with high carboxyl content. Background Art
[0002] Among many renewable resources, lignocellulosic biomass represented by crop straw and forest residues is considered to be the most promising renewable resource to replace petrochemical resources due to its rich content of cellulose, hemicellulose and lignin. Common methods for preparing cellulose nanofibers include mechanical methods, chemical methods and biological treatment methods, each of which has its own advantages and disadvantages. In recent years, researchers have discovered a method for selectively oxidizing cellulose primary alcohol hydroxyl groups in aqueous solution using the TEMPO / NaBr / NaClO system, which provides a new approach for the preparation of cellulose nanofibers. The nanofibers prepared by this method can be stably dispersed in water. The introduction of carboxyl groups into cellulose has broad application potential in organic synthesis, biochemistry, cosmetics, medicine and materials science.
[0003] Natural cellulose (bleached pulp, cotton) can be decomposed into individual microfibers after 2,2,6,6-tetramethylpiperidin-1-oxide (TEMPO) free radical-mediated oxidation and homogenization mechanical treatment. TEMPO catalyzes the oxidation of cellulose C6-aldehyde groups to generate C6-carboxyl groups. NaClO (sodium hypochlorite) is the main oxidant in this process. It first reacts with NaBr to form NaBrO. Then NaBrO oxidizes TEMPO into nitrite ions. Nitrite ions oxidize primary alcohol hydroxyls into aldehyde groups (intermediates) and finally generate carboxyl groups. In the treatment process of papermaking wastewater, the ferrous ion Fenton method has gradually become the mainstream process for desizing wastewater treatment. Fenton reagent (fenton) is a ferrous ion (Fe 2+ ) is a wastewater treatment method that uses hydrogen peroxide (H2O2) as a catalyst for chemical oxidation. It can generate strongly oxidizing hydroxyl radicals, which react with refractory organic matter in aqueous solution to generate organic radicals to destroy their structure and eventually oxidize and decompose. It mainly degrades organic pollutants in papermaking wastewater by adding ferrous sulfate and hydrogen peroxide to the wastewater to generate hydroxyl radicals (strong oxidation). Ferrous ion Fenton reagent can be appropriately applied to the pretreatment of natural cellulose, so that the cellulose is treated to obtain hydroxyl radicals for oxidation to aldehydes or carboxyls. From the perspective of the redox electrode potential formed by physicochemical point of view, sodium chlorite is slightly stronger than sodium hypochlorite. From the perspective of organic chemistry, in terms of the oxidation ability of primary alcohols, sodium hypochlorite oxidizes most of the primary alcohols into aldehydes and a small part into acids, while sodium chlorite oxidizes most of the primary alcohols into acids.
[0004] There are many methods for preparing CNC-COOHs by introducing carboxyl groups, the most common of which are TEMPO / NaBr / NaClO system oxidation method, KMnO4 oxidation method, sodium chlorite oxidation method, periodate oxidation method, etc. However, when preparing nanocellulose with high carboxyl content, the carboxyl content obtained by treating the raw materials with a single oxidant is limited, and subsequent treatments such as re-oxidation or increasing the reaction time are often required. Therefore, how to prepare nanocellulose with high carboxyl content through a reasonable oxidation system and steps is an important factor in expanding the application of nanocellulose. In addition, there is no method for preparing high carboxyl transparent nanocellulose by using sodium hydroxide to pretreat the raw materials, and then using Fenton's reagent (fenton) with TEMPO / NaBr / NaClO system and NaClO2 system as oxidants, and co-oxidizing in three steps combined with high-pressure homogenization to treat the oxidation products. Summary of the invention
[0005] Purpose of the invention: The technical problem to be solved by the present invention is to provide a method for preparing transparent nanocellulose with a high carboxyl content in view of the shortcomings of the prior art.
[0006] The technical problem that the present invention needs to solve is to propose the application of the transparent nanocellulose.
[0007] In order to solve the above technical problems, the present invention discloses a method for preparing transparent nanocellulose with a high carboxyl content, comprising the following steps:
[0008] Step 1, sodium hydroxide pretreatment: adding the absolutely dry cellulose raw material into a sodium hydroxide solution prepared with deionized water, adjusting the pH to neutral after swelling, and then beating into a slurry;
[0009] Step 2, using Fenton's reagent to perform a first oxidation treatment on the slurry to obtain a treatment product;
[0010] Step 3, the treated product obtained in step 2 is subjected to a second oxidation step using a TEMPO-NaBr-NaClO system to obtain aldehyde / carboxyl cellulose;
[0011] Step 4, the aldehyde / carboxyl cellulose obtained in step 3 is subjected to a third step oxidation using NaClO2 to obtain an oxidation primary product;
[0012] Step 5: Mechanically treat the initial oxidation product obtained in step 4 to obtain transparent nanocellulose with a high carboxyl content.
[0013] Furthermore, the specific operation of step 1 is: using deionized water to prepare a sodium hydroxide solution with a mass fraction of 5-10%, then crushing the absolutely dry cellulose raw material and adding it to the sodium hydroxide solution to swell for 5-10 hours, using 0.1-0.3 mol / L hydrochloric acid solution to adjust the pH to neutral and then beat it into a slurry, filtering the slurry, and drying it at 60-80° C. for standby use;
[0014] The cellulose raw material is bleached coniferous pulp, eucalyptus broadleaf pulp or cotton pulp; the crushing / pulping equipment is one or more of a handheld food processor, a wall breaking machine and a soy milk machine.
[0015] Furthermore, the specific operation of step 2 is: taking the absolutely dry cellulose raw material after the sodium hydroxide pretreatment, adding deionized water to soak, and then adding Fenton reagent to mix and react, reacting at a temperature of 55 to 70° C. for 3 to 10 hours, washing with deionized water and filtering after the reaction is completed, drying the filter residue at 70° C., and finally storing it in a refrigerator at 5° C. for future use;
[0016] The mixing ratio of cellulose raw material and deionized water in the slurry is 1:10-1:20; the Fenton reagent is a solution prepared by ferrous chloride tetrahydrate and hydrogen peroxide; the molar ratio of the mass of cellulose raw material and hydrogen peroxide in the slurry is 1g:15-20mmol, and the mass ratio of cellulose raw material and ferrous chloride tetrahydrate in the slurry is 1:0.015-0.03.
[0017] Furthermore, the specific operation of step 3 is as follows: dispersing the treated product obtained in step 2 in deionized water to form a slurry, then sequentially adding TEMPO and NaBr in proportion, stirring and dissolving, adding sodium hypochlorite solution, maintaining the pH at 10 to 11 for reaction until the pH no longer changes, washing and filtering with deionized water / centrifuging after the reaction is completed, and placing the filter residue in a refrigerator at 0 to 10° C. for storage;
[0018] The pulping equipment is one or more of a handheld food processor, a wall breaking machine and a soy milk machine; the reaction temperature is 10-20°C, the mixing ratio of the cellulose raw material and deionized water is 1:100-1:150, the mass ratio of the cellulose raw material to TEMPO is 1:0.01-0.02, the mass ratio of TEMPO to NaBr is 1:10, and 4-6 mmol sodium hypochlorite is added for each gram of cellulose raw material for oxidation; the pH is regulated using 0.1 mol / L sodium hydroxide and 0.5 mol / L hydrochloric acid.
[0019] Furthermore, the specific operation of step 4 is: further oxidizing the aldehyde / carboxyl cellulose obtained in step 3 with NaClO2 at pH 4-5, washing and filtering with deionized water after the reaction is completed, and drying the filter residue at 70° C. for later use;
[0020] The reaction temperature is 10-20°C, and the mixing ratio of cellulose raw material to deionized water is 1:100-
[0021] 1:200; the mass ratio of cellulose raw material to NaClO2 is 1:0.1-0.2; the pH is regulated using sodium hydroxide and hydrochloric acid.
[0022] Furthermore, the specific operation of step 5 is: dispersing the initial oxidation product obtained in step 4 in water, and then circulating homogenizing in a high-pressure homogenizer, the homogenization pressure is 100-150MP, the number of cycles is 3-10 times, the homogenization temperature is 10-60°C, the solid content is 2-4%, and finally transparent nanocellulose with a high carboxyl content is obtained.
[0023] The present invention further proposes the use of the transparent nanocellulose obtained by the preparation method in the preparation of cosmetics.
[0024] In one embodiment, the cosmetic is a sunscreen.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The present invention starts with pretreatment, pretreating the raw materials with sodium hydroxide, using Fenton's reagent (H2O2+Fe 2+ ), TEMPO-NaBr-NaClO system and sodium chlorite as multiple oxidation to obtain cellulose with high carboxyl content, and then high-pressure homogenization treatment is performed to obtain transparent nanocellulose colloid with high carboxyl content. The operation method of the present invention is simple, the operation process is safe and the product yield is high. In addition, the present invention increases the degree of oxidation of natural cellulose raw materials, increases the carboxyl content of the oxidized product, and improves the transparency of the product, thereby obtaining a wider range of applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a processing flow chart of the present invention;
[0028] Figure 2 The product pictures of each embodiment and comparative example are real pictures, and the solid content of each sample is 2%; wherein, a is a real picture of the product of embodiment 1; b is a real picture of the product of embodiment 2; c is a real picture of the product of embodiment 3; d is a real picture of the product of comparative example 1; e is a real picture of the product of comparative example 2;
[0029] Figure 3 This is a scanning electron microscope (SEM) photograph of the product obtained after homogenizing the oxidized cellulose in Example 1. DETAILED DESCRIPTION
[0030] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.
[0031] Embodiment 1, as Figure 1 As shown, a method for preparing transparent nanocellulose with a high carboxyl content provided by an embodiment of the present invention comprises the following steps:
[0032] 1) Sodium hydroxide pretreatment: Use deionized water to prepare 300 ml of 5% sodium hydroxide solution, then take 15g of absolutely dry sulfate bleached coniferous pulp cellulose raw material, grind it and add it into the sodium hydroxide solution to swell for 10 hours, adjust the pH to neutral and then make a slurry, filter the slurry, and dry it at 70°C for use.
[0033] 2) Fenton reagent treatment: Take 10g of sulfate bleached coniferous pulp cellulose raw material treated with sodium hydroxide, and use a wall breaker or grinder to finely crush it to ensure that the raw material is fully crushed. Subsequently, the crushed raw material is transferred to a conical flask with a capacity of 1000ml. Then, 200ml of deionized water is added to the conical flask to fully infiltrate the raw material, and this infiltration lasts for 1h. After the infiltration is completed, 0.25g of ferrous chloride tetrahydrate is added to the conical flask, and then 100ml of hydrogen peroxide solution with a concentration of 1.76mol / L is added. After mixing evenly, the conical flask is placed in a constant temperature water bath to ensure that the reaction temperature is maintained at 70°C, and the reaction is carried out under this condition for 10h. After the reaction is completed, the reaction mixture is washed and filtered with deionized water to remove excess solution and impurities. The obtained filter residue is dried at 70°C for standby use.
[0034] 3) TEMPO-NaBr-NaClO system treatment: First, take 6g of dry cellulose after oxidation treatment with Fenton reagent and add it to a beaker containing 600ml of deionized water. Subsequently, the cellulose was evenly dispersed using a handheld food processor to form a cellulose slurry. Then, 0.075g of TEMPO and 0.75g of sodium bromide were added to the cellulose slurry, and stirred for 30min to ensure that they were fully dissolved and mixed evenly. Then 18g of sodium hypochlorite solution with an effective chlorine content of 13% was added, and a magnetic stirrer was started for reaction. During the reaction, 0.1mol / L of sodium hydroxide and 0.5mol / L of hydrochloric acid were used to accurately control the pH value of the reaction system to maintain it at 10.5. The reaction was continued until the pH value remained stable and no longer changed. After the reaction, the product was repeatedly washed with deionized water and centrifuged to obtain the precipitate. Until the product reached a neutral state. TEMPO-oxidized nanocellulose, i.e., aldehyde-carboxyl TCONs, was obtained. The centrifuged product was placed in a refrigerator and stored at a low temperature of 5°C for subsequent use.
[0035] 4) Sodium chlorite treatment: Take 5 g of the cellulose product after oxidation by Fenton reagent and TEMPO-NaBr-NaClO system and place it in a 1000 ml conical flask, add 500 ml of deionized water and stir for 30 min to disperse evenly, use 0.1 mol / L hydrochloric acid to adjust the pH to 4.0, then add 0.5 g of sodium chlorite solid to the conical flask, control the temperature at 10°C, stir and react for 5 hours, wash and filter the product with deionized water after the reaction, and dry the precipitate at 70°C for later use.
[0036] 5) High-pressure homogenization treatment: Take 5 g of cellulose oxidized by Fenton reagent, TEMPO-NaBr-NaClO system, and sodium chlorite, add deionized water to prepare a liquid with a solid content of 2%, place it in a high-pressure homogenizer for cyclic homogenization, set the homogenization pressure at 100 MP (1000 Bar), cycle 5 times, and homogenize at a temperature of 20° C., and a transparent nanocellulose product with a high carboxyl content can be obtained. Figure 3 This is a scanning electron microscope (SEM) photograph of the product obtained after homogenizing the oxidized cellulose in Example 1.
[0037] Example 2: A method for preparing transparent nanocellulose with a high carboxyl content provided by an embodiment of the present invention comprises the following steps:
[0038] 1) Sodium hydroxide pretreatment: The only difference from 1) in Example 1 is that the cellulose raw material is eucalyptus hardwood pulp;
[0039] 2) Fenton's reagent treatment: The only difference from 2) in Example 1 is that 10 g of eucalyptus hardwood pulp cellulose raw material treated with sodium hydroxide is taken;
[0040] 3) TEMPO-NaBr-NaClO system treatment: the same as 3) in Example 1;
[0041] 4) Sodium chlorite treatment: the same as 4) in Example 1;
[0042] 5) High-pressure homogenization treatment: the same as 5) in Example 1.
[0043] Example 3: A method for preparing transparent nanocellulose with a high carboxyl content provided by an embodiment of the present invention comprises the following steps:
[0044] 1) Sodium hydroxide pretreatment: The only difference from 1) in Example 1 is that cotton pulp is used as the cellulose raw material;
[0045] 2) Fenton's reagent treatment: The only difference from 2) in Example 1 is that 10 g of cotton pulp cellulose raw material treated with sodium hydroxide is taken;
[0046] 3) TEMPO-NaBr-NaClO system treatment: the same as 3) in Example 1;
[0047] 4) Sodium chlorite treatment: the same as 4) in Example 1;
[0048] 5) High-pressure homogenization treatment: the same as 5) in Example 1.
[0049] Comparative Example 1: A method for preparing transparent nanocellulose with a high carboxyl content provided by an embodiment of the present invention comprises the following steps:
[0050] 1) Sodium hydroxide pretreatment: the same as 1) in Example 1;
[0051] 2) Fenton reagent treatment: the same as 2) in Example 1;
[0052] 3) TEMPO-NaBr-NaClO system treatment: the same as 3) in Example 1;
[0053] 4) Sodium chlorite treatment: the same as 4) in Example 1.
[0054] Comparative Example 2: A method for preparing transparent nanocellulose with a high carboxyl content provided by an embodiment of the present invention comprises the following steps:
[0055] 1) TEMPO-NaBr-NaClO system treatment: First, take 6g of absolutely dry sulfate bleached conifer pulp cellulose raw material and add it to a beaker containing 600ml of deionized water. Subsequently, the cellulose was evenly dispersed using a handheld food processor to form a cellulose slurry. Then, 0.075g of TEMPO and 0.75g of sodium bromide were added to the cellulose slurry respectively, and stirred for 30min to ensure that they were fully dissolved and mixed evenly. Then 18g of sodium hypochlorite solution with an effective chlorine content of 13% was added, and a magnetic stirrer was started for reaction. During the reaction, 0.1mol / L of sodium hydroxide and 0.5mol / L of hydrochloric acid were used to accurately control the pH value of the reaction system to maintain it at 10.5. The reaction was continued until the pH value remained stable and no longer changed. After the reaction was completed, the product was repeatedly washed with deionized water and centrifuged to obtain the precipitate. Until the product reached a neutral state. TEMPO-oxidized nanocellulose, i.e., aldehyde-carboxyl TCONs, was obtained. The centrifuged product was placed in a refrigerator and stored at a low temperature of 5°C for subsequent use.
[0056] 2) High-pressure homogenization treatment: the same as 5) in Example 1.
[0057] The products obtained in Examples 1 to 3 and Comparative Examples 1 and 2 were subjected to the following tests:
[0058] (1) Solid content: The drying method was used, and the sample solid content was 2% by adding deionized water and product.
[0059] (2) Carboxyl content was determined using the conductivity method.
[0060] (3) Transmittance: The transmittance at 600 nm was measured using ultraviolet spectrophotometry.
[0061] (4) Particle size range: measured using a scanning electron microscope.
[0062] The above characterizations were tested several times. The transmittance had a certain error each time due to sampling reasons.
[0063] The results are shown in Table 1:
[0064] Table 1
[0065]
[0066] Through Table 1 and Figure 2 It can be seen that, by comparing Example 1 with Example 2 and Example 3, the selection of the above three raw materials can obtain nanocellulose with a higher carboxyl content through this method, and the transmittance at 600nm in a 2% solid content dispersion can exceed 80%; comparing the products prepared in Example 1 and Comparative Example 1, because high-pressure homogenization was not performed, the product obtained in Comparative Example 1 has a low transmittance and is easy to precipitate, indicating that the diameter of the cellulose fiber is not nanometer-scale and the dispersion performance is poor, and the product subjected to high-pressure homogenization is more likely to obtain nanometer-scale transparent cellulose; comparing Example 1 with Comparative Example 2, it can be found that the raw materials treated with sodium hydroxide and multiple oxidants can increase the carboxyl content of the cellulose raw materials compared with oxidation using the TEMPO-NaBr-NaClO system alone, and a higher carboxyl content has certain advantages in homogenizing and preparing transparent nanocellulose.
[0067] The above are only preferred embodiments of the present invention. It should be pointed out that, for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention. These should also be regarded as the protection scope of the present invention. These will not affect the effect of the implementation of the present invention and the practicality of the patent.
Claims
1. A method for preparing transparent nanocellulose with a high carboxyl content, characterized in that: The following steps are involved: Step 1, sodium hydroxide pretreatment: adding the absolutely dry cellulose raw material into a sodium hydroxide solution prepared with deionized water, adjusting the pH to neutral after swelling, and then beating into a slurry; Step 2, using Fenton's reagent to perform a first oxidation treatment on the slurry to obtain a treatment product; Step 3, the treated product obtained in step 2 is subjected to a second oxidation step using a TEMPO-NaBr-NaClO system to obtain aldehyde / carboxyl cellulose; Step 4, the aldehyde / carboxyl cellulose obtained in step 3 is subjected to a third step oxidation using NaClO2 to obtain an oxidation primary product; Step 5: Mechanically treat the initial oxidation product obtained in step 4 to obtain transparent nanocellulose with a high carboxyl content.
2. The preparation method according to claim 1, characterized in that: The specific operation of step 1 is: using deionized water to prepare a sodium hydroxide solution with a mass fraction of 5-10%, then crushing the absolutely dry cellulose raw material and adding it to the sodium hydroxide solution to swell for 5-10 hours, using 0.1-0.3 mol / L hydrochloric acid solution to adjust the pH to neutral and then beat it into a slurry, filtering the slurry, and drying it at 60-80° C. for later use; The cellulose raw material is bleached kraft conifer pulp, eucalyptus hardwood pulp or cotton pulp.
3. The preparation method according to claim 2, characterized in that: The specific operation of step 2 is: taking the absolutely dry cellulose raw material after the sodium hydroxide pretreatment, adding deionized water to soak, and then adding Fenton reagent to mix and react, reacting at a temperature of 55-70° C. for 3-10 hours, washing with deionized water and filtering after the reaction is completed, drying the filter residue at 70° C., and finally storing it in a refrigerator at 5° C. for future use; The mixing ratio of cellulose raw material and deionized water in the slurry is 1:10-1:20; the Fenton reagent is a solution prepared by ferrous chloride tetrahydrate and hydrogen peroxide; the molar ratio of the mass of cellulose raw material and hydrogen peroxide in the slurry is 1g:15-20mmol, and the mass ratio of cellulose raw material and ferrous chloride tetrahydrate in the slurry is 1:0.015-0.
03.
4. The preparation method according to claim 1, characterized in that: The specific operation of step 3 is as follows: dispersing the treated product obtained in step 2 in deionized water to form a slurry, then sequentially adding TEMPO and NaBr in proportion, stirring and dissolving, adding sodium hypochlorite solution, maintaining the pH at 10-11 for reaction until the pH no longer changes, washing and filtering with deionized water / centrifuging after the reaction is completed, and placing the filter residue in a refrigerator at 0-10° C. for storage for later use; The reaction temperature is 10-20°C, the mixing ratio of cellulose raw material and deionized water is 1:100-1:150, the mass ratio of cellulose raw material and TEMPO is 1:0.01-0.02, the mass ratio of TEMPO and NaBr is 1:10, and 4-6 mmol sodium hypochlorite is added for each gram of cellulose raw material for oxidation; the pH is regulated using 0.1 mol / L sodium hydroxide and 0.5 mol / L hydrochloric acid.
5. The preparation method according to claim 1, characterized in that: The specific operation of step 4 is: further oxidizing the aldehyde / carboxyl cellulose obtained in step 3 with NaClO2 at pH 4-5, washing and filtering with deionized water after the reaction is completed, and drying the filter residue at 70°C for later use; Among them, the reaction temperature is 10~20℃, the mixing ratio of cellulose raw material and deionized water is 1:100~1:200; the mass ratio of cellulose raw material and NaClO2 is 1:0.1~0.2; and the pH is regulated using sodium hydroxide and hydrochloric acid.
6. The preparation method according to claim 1, characterized in that: The specific operation of step 5 is: dispersing the initial oxidation product obtained in step 4 in water, and then circulating homogenizing in a high-pressure homogenizer, the homogenization pressure is 100-150MP, the number of cycles is 3-10 times, the homogenization temperature is 10-60°C, the solid content is 2-4%, and finally transparent nanocellulose with a high carboxyl content is obtained.
7. Use of the transparent nanocellulose obtained by the preparation method according to any one of claims 1 to 6 in the preparation of cosmetics.
8. The use according to claim 7, characterized in that: The cosmetic is a sunscreen.
Citation Information
Cited By
Preparation method of flame-retardant recombined bamboo
CN120503292A